HUBUNGAN TINGKAT PENGETAHUAN DENGAN TINGKAT KECEMASAN MASYARAKAT KOTA KUPANG TERHADAP VAKSIN COVID-19 - Putu Dinda Pramesti; Ika Febrianti Buntoro; I Made Artawan; Christina Olly Lada (Jurnal Kesehatan Masyarakat (Undip), 2022)
"COVID-19" (Coronavirus Disease 2019) was officially announced by WHO on February 11th, 2020 as a new disease. SARS-CoV-2 infection in humans causes symptoms of acute respiratory disorders.‎ In NTT province there has been 6,365 confirmed positive corona, with 2,924 of whom were in Kupang City.‎ One way to prevent the spread of the pandemic is with a vaccine. In Kupang City, 39,896 or 4.54% of the provincial target had received stage 1 and 2 of vaccinations. This was still far from the expected target. To find out the relationship between the knowledge level and the anxiety level of the community of Kupang City on the COVID-19 vaccine. This research was an observational analytic study using a cross-sectional method. The sample in this study was selected using non-probability sampling with a total of 232 respondents. This study was analyzed by univariate and bivariate analysis using the Somers'd correlation test, after that a comparative test using Mann Whitney. The results showed that 220 respondents (94.8%) had a good knowledge level, 9 respondents (3.9%) had a moderate knowledge level and 3 respondents (1.3%) had a low knowledge level. Then 224 respondents (96.6%) did not experience anxiety disorders, 7 respondents (3.0%) had mild anxiety disorders, and 1 respondent (0.4%) had moderate anxiety disorders. The results of the bivariate test using the Somers'd correlation test showed p = 0.022 or p < 0.05 indicating that there was a significant relationship between the knowledge level and the anxiety level of the community of Kupang City on the COVID-19‎ vaccine. The results of the Mann Whitney test showed p = 0.497 or p > 0.05 indicating that there was no significant difference between the anxiety levels of respondents who have not and those who have received the COVID-19 vaccine. There was a significant relationship between the knowledge level and the anxiety level of the community of Kupang City on the COVID-19‎ vaccine. There was no significant difference between the anxiety level of respondents who have not and those who have received the COVID-19 vaccine‎.